Mối tương quan giữa các giá trị Magnitud động đất tính theo thang Magnitud của Việt Nam và theo số liệu Quốc tế - Lư, Ngô Thị (Vietnam Journal of Earth Sciences, 2003)
Relatlon between magnitude values of earthquakes determlned by magnitude scale of Vletnam and by data ofthe Internatlonal Selsmologlcal Center (lSC)